1996
DOI: 10.1111/j.1476-5381.1996.tb16030.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of selective phosphodiesterase 3 and 4 isoenzyme inhibitors and established anti‐asthma drugs on inflammatory cell activation

Abstract: 1 This study aimed to evaluate the effects of phosphodiesterase (PDE) inhibitors and currently prescribed anti-asthma drugs for their ability to inhibit inflammatory cell activation in vitro. 2 Alveolar macrophages and eosinophils were isolated from the bronchoalveolar lavage (BAL) fluid of ovalbumin (Ovalb)-sensitized guinea-pigs. Opsonized zymosan (OZ) and PAF stimulated leukotriene B4 (LTB4) release from eosinophils was measured by radioimmunoassay. Ovalb-induced superoxide generation was measured by reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 26 publications
(32 reference statements)
3
26
0
Order By: Relevance
“…The release of arachidonate was significantly reduced upon oral treatment of the guinea-pigs by the selective PDE4 inhibitors rolipram and Ro 20-1724, but not by the selective PDE3 inhibitor milrinone. In agreement with a previous study on the reduced activity of guinea-pig alveolar macrophages by PDE4 inhibitors [30], the present data confirm the potential interest of selective PDE4 inhibitors as anti-inflammatory drugs. It was previously demonstrated that, at the same doses, rolipram and Ro 20-1724 significantly reduced the recruitment of eosinophils in guinea-pigs induced by OA challenge, platelet-activating factor or interleukin-5 [16,31].…”
Section: Discussionsupporting
confidence: 81%
“…The release of arachidonate was significantly reduced upon oral treatment of the guinea-pigs by the selective PDE4 inhibitors rolipram and Ro 20-1724, but not by the selective PDE3 inhibitor milrinone. In agreement with a previous study on the reduced activity of guinea-pig alveolar macrophages by PDE4 inhibitors [30], the present data confirm the potential interest of selective PDE4 inhibitors as anti-inflammatory drugs. It was previously demonstrated that, at the same doses, rolipram and Ro 20-1724 significantly reduced the recruitment of eosinophils in guinea-pigs induced by OA challenge, platelet-activating factor or interleukin-5 [16,31].…”
Section: Discussionsupporting
confidence: 81%
“…PDE III-selective inhibitors have shown inhibitory activity on monocyte-derived TNF-a production and on neutrophil-derived leukotriene production (Banner et al, 1996;Schudt et al, 1991). In our assay, the PDE III-selective inhibitors were also active but to a lesser extent than the PDE4 inhibitors.…”
Section: Discussionmentioning
confidence: 61%
“…Whereas PDE4 inhibitors are efficacious inhibitors of proinflammatory mediator release from certain cell types, there is evidence to suggest that dual inhibition of PDE3 and PDE4 is additive or synergistic at suppressing the activation/ functions of other cell types (e.g., macrophages, dendritic cells, epithelial cells, lymphocytes, and endothelial cells) (Banner et al, 1996;Giembycz et al, 1996;Blease et al, 1998;Wright et al, 1998;Gantner et al, 1999;Hatzelmann and Schudt, 2001;Banner and Press, 2009) but are not effective at relaxing ASM in vitro and do not cause acute bronchodilation experimentally (Boswell-Smith et al, 2006a) or clinically (Grootendorst et al, 2003). In contrast, PDE3 inhibitors are able to relax human ASM (Matera et al, 2011b) and can elicit bronchodilation in humans (Myou et al, 1999(Myou et al, , 2003.…”
Section: Introductionmentioning
confidence: 99%